The immune checkpoint adenosine 2A receptor is associated with aggressive clinical outcomes and reflects an immunosuppressive tumor microenvironment in human breast cancer - Zohair, Basma; Chraa, Dounia; Rezouki, Ibtissam; Benthami, Hamza; Razzouki, Ibtissam; Elkarroumi, Mohamed; Olive, Daniel; Karkouri, Mehdi; Badou, Abdallah (Frontiers in Immunology, 2023)
The crosstalk between the immune system and cancer cells has aroused considerable interest over the past decades. To escape immune surveillance cancer cells evolve various strategies orchestrating tumor microenvironment. The discovery of the inhibitory immune checkpoints was a major breakthrough due to their crucial contribution to immune evasion. The A2AR represents one of the most essential pathways within the TME. In addition to its involvement in several processes such as hypoxia, tumor progression, and chemoresistance, A2AR is linked to unfavorable prognosis in several cancers. However, its clinical significance in human breast cancer remains elusive. This study is the first to elucidate the clinical and immunological relevance of A2AR in breast cancer patients. The mRNA expression profile and protein analysis revealed increased expression of A2AR within breast tumors. This overexpression was associated with high grade, elevated Ki-67, aggressive molecular subtypes and poor survival. Interestingly, A2AR expression on tumor-infiltrating immune cells correlated positively with PD-1 and negatively with CTLA-4. Analysis of large-scale microarray data from METABRIC cohort consistently depicted the association between A2AR and adverse clinical outcomes. We performed digital cytometry to estimate the abundance of cell populations. The analysis was run on RStudio software version (7.8 + 2023.03.0) with EPIC, CIBERSORT and ImmuneCellAI bioinformatics algorithms. Tumor purity, stromal and immune scores were calculated using the ESTIMATE computational method. A2AR distribution within TME cells was investigated at the single cell level using the TISCH scRNA-seq database. Our findings disclosed more profuse infiltration of protumoral cells such as M0 and M2 macrophages, Tregs, endothelial and exhausted CD8+ T cells within A2ARhigh tumors. According to the Single-Cell database, A2AR is expressed in malignant, stromal and immune cells. Moreover, A2AR is related to tumor purity, stromal and immune scores. Our results also revealed that CD8+T cells from A2ARhigh patients exhibited an exhausted functional profile. Finally, GSEA analysis highlighted the association of A2AR with signaling pathways and biological mechanisms involved in tumor escape and progression, including immunosuppression, invasion, proliferation and metastasis. In light of these findings, A2AR could be deemed a promising therapeutic target to overcome immune evasion prevailing within the TME of breast cancer patients